Effect of perioperative sodium bicarbonate administration on renal function following cardiac surgery for infective endocarditis: a randomized, placebo-controlled trial. Issue 1 (December 2017) - Cho, Jin; Soh, Sarah; Shim, Jae-Kwang; Kang, Sanghwa; Choi, Haegi; Kwak, Young-Lan
Abstract Background Patients with infective endocarditis (IE) have an elevated risk of renal dysfunction because of extensive systemic inflammation and use of nephrotoxic antibiotics. In this randomized, placebo-controlled trial, we investigated whether perioperative sodium bicarbonate administration could attenuate postoperative renal dysfunction in patients with IE undergoing cardiac surgery. Methods Seventy patients randomly received sodium chloride (n  = 35) or sodium bicarbonate (n  = 35). Sodium bicarbonate was administered as a 0.5 mmol/kg loading dose for 1 h commencing with anesthetic induction, followed by a 0.15 mmol/kg/h infusion for 23 h. The primary outcome was peak serum creatinine (SCr) level during the first 48 h postoperatively. The incidence of acute kidney injury, SCr level, estimated glomerular filtration rate, and major morbidity endpoints were assessed postoperatively. Results The peak SCr during the first 48 h postoperatively (bicarbonate vs. control: 1.01 (0.74, 1.37) mg/dl vs. 0.88 (0.76, 1.27) mg/dl, P  = 0.474) and the incidence of acute kidney injury (bicarbonate vs. control: 29% vs. 23%, P  = 0.584) were similar in both groups. The postoperative increase in SCr above baseline was greater in the bicarbonate group than in the control group on postoperative day 2 (0.21 (0.07, 0.33) mg/dl vs. 0.06 (0.00, 0.23) mg/dl, P  = 0.028) and postoperative day 5 (0.23 (0.08, 0.36) mg/dl vs. 0.06 (0.00, 0.23) mg/dl, P  = 0.017). Conclusions Perioperative sodium bicarbonate administration had no favorable impact on postoperative renal function and outcomes in patients with IE undergoing cardiac surgery. Instead, it was associated with possibly harmful renal effects, illustrated by a greater increase in SCr postoperatively, compared to control. Trial registration ClinicalTrials.gov, NCT01920126 . Registered on 31 July 2013.